(untitled) (Research, Society and Development, 2021)
The objective of this work was to describe the characteristics of orofacial harmonization courses offered to dentists in a city in the Northwest region of Paraná. This is an observational, descriptive and cross-sectional study in which data were collected from information searches on websites of educational institutions, social networks and the Google platform, with the following keywords: "course" + " matching” or “facial matching” or “orofacial matching” or “botulinum toxin” or “botox” or “filling” or “hyaluronic acid”, limiting the search to a city. This resulted in 20 courses, whose therapeutic and aesthetic purposes of the procedures were included in the syllabus of 85% of the courses, while in 15% there were only aesthetic objectives. 75% of the courses were called immersion, 15% were specializations, while 10% were improvements. 85% reported working hours and, in 73.68% of these, the duration was less than or equal to five days. The amount of hours/class charged to students ranged from R65.00 to R1,000.00. It is concluded that the orofacial harmonization courses offered are of high value, compared to courses in other specialties, and are mostly of short duration. In addition, there was a need for the entities promoting the courses to be alerted to the adequacy of the name or type (updating, perfecting, specialization, among others) to the minimum workload required.